The interplay between bacterial biofilms, encrustation, and wall shear stress in ureteral stents: a review across scales - Amado, Pedro; Zheng, Shaokai; Lange, Dirk; Carugo, Dario; Waters, Sarah L.; Obrist, Dominik; Burkhard, Fiona; Clavica, Francesco (Frontiers in Urology, 2024)
Ureteral stents are hollow tubes that are inserted into the ureter to maintain the flow of urine from the kidney to the bladder. However, the use of these indwelling stents is associated with potential complications. Biofilm, an organized consortium of bacterial species embedded within a selfproducing extracellular matrix, can attach to the outer and inner surfaces of ureteral stents. Furthermore, encrustation -defined as the buildup of mineral deposits on the stent surface -can occur independently or in parallel with biofilm formation. Both phenomena can cause stent obstruction, which can lead to obstructive pyelonephritis and make stent removal difficult. Understanding the influence of flow on the development of biofilm and encrustation and the impact of small mechanical environmental changes (e.g., wall shear stress distribution) is key to improve the long-term performance of stents. Identifying the optimal stent properties to prevent early bacterial attachment and/or crystal deposition and their growth, would represent a breakthrough in reducing biofilm-/encrustation-associated complications. This review identifies the most prevalent bacterial strains and crystals associated with ureteral stents, and their process of association with the stent surface, which often depends on patient comorbidities, stent material, and indwelling time. Furthermore, we focus on the often-overlooked role of fluid dynamics on biofilm and encrustation development in ureteral stents, across a range of physical scales (i.e., from micro-to macro-scale) with the aim of providing a knowledge base to inform the development of safer and more effective ureteral stents.